Ethnomedicinal Plants Used by the Populations of the Central High Atlas of Morocco for the Prevention and Relief of the Main Symptoms Similar to Coronavirus Diseases - Abdelaziz Moujane; Abdellah Ouigmane; Elhoucein Layati; Abdelali Boulli (PT FORMOSA CENDEKIA GLOBAL, 2022)
In Morocco, the population has used several medicinal plants to relieve and prevent against covid-19. The data were collected through questionnaires and other means (Telephone, WhatsApp, Facebook).The information collected from the survey also showed that the inhabitants of the Central High Atlas of Azilal use during covid-19 a total of 50 species of medicinal plants belonging to 18 families. Based on the ICF value the five symptoms treated were the fever (ICF = 0.90), followed by cough (ICF = 0.79), headache with (ICF = 0.68), breathing difficulties (ICF = 0.61), diarrhea (ICF=0.31), and fatigue (ICF = 0.22). The results showed that medicinal plants in the study area occupy an important place in the treatment of the principles similar to those of the coronavirus.